The Correlation between the Use of Grok AI as a Teaching Medium and Students’ Digital Literacy - Fauzi, Fadilah Nur; Zahra, Intan Karima; Aisyah, Siti; Syahroni, Abdul Rozak; Ramadhan, Dhani Ringga; Khasanah, - (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
This study aimed to explore the relationship between the utilization of Grok AI as a teaching tool and the digital literacy of students. To achieve this, a quantitative research approach was adopted, involving 30 university students from different universities in West Java and Jakarta. Data were gathered using a questionnaire designed with a five-point Likert scale and were analyzed using descriptive statistics along with the Pearson correlation test. The results indicated that students exhibited a very high level of digital literacy, while their engagement with Grok AI was found to be at a moderate to high level. Additionally, a statistically significant positive correlation was identified between the two variables, with r = .364 and p = .048. This suggests that increased usage of Grok AI in educational settings leads to higher levels of digital literacy among students. However, the varying proficiency levels imply that additional factors could influence students' digital literacy. Consequently, Grok AI can be viewed as an important educational resource, but it requires further integration strategies and support systems to enhance its effectiveness in developing students’ skills.